MANAGING SOCIAL INNOVATION IN CROWDFUNDING DIGITAL PLATFORM - Halimatus Sadiyah; Ika Diyah Candra (Airlangga Journal of Innovation Management, 2020)
ABSTRACTIntractable social and economic problems are increasingly complex in developing countries caused by a discrepancy between economic growth and equitable welfare. The government policy on one hand and market solution, on the other hand, have proved inadequate since lacks of incentives, appropriate model and support from the market to tackle its externalities while the civil society lacks resources, ideas and skills to scale. Therefore, the collaboration concept to solve this problem arisen by crowdsourcing, especially crowd funding business model. This study aims to identify and analyze how crowdfunding digital platform managing their social innovation and how social innovation networks support them to achieve their goals.  This research is descriptive qualitative research with the study of literature, participatory observation and interviews on crowdsourcing platforms as the data collection method to Indonesian crowdfunding platforms: Kitabisa.com and Gandeng Tangan. As a social innovation, the two companies have different social innovation networks but apply similar stages of social innovation, from the stage of idea formulation to scaling and diffusion of innovation, but both are still in the development stage to create a systemic impact on social innovation as a whole. This research is expected to have practical implications for social innovation empowerment that initiated by the government or private sector and theoretical implication about the development of collaboration-based innovation management to solve social and economic problems. The novelty of research of this research lies in the focus of research that discusses the role of crowdfunding platforms in creating social innovation that has not been much studied in Indonesia. Keywords: social innovation, Indonesia, socio and economic problems, crowdfunding, digital platform. ABSTRAKMasalah-masalah sosial dan ekonomi yang tak terelakkan semakin kompleks di negara-negara berkembang yang disebabkan oleh perbedaan antara pertumbuhan ekonomi dan kesejahteraan yang adil. Kebijakan pemerintah tidak mungkin menyelesaikan beberapa masalah yang paling mendesak — seperti kemiskinan, perubahan iklim, pengangguran, penyakit pandemi, dan meluasnya kesenjangan kesejahteraan. Kebijakan pemerintah di satu sisi dan solusi pasar, di sisi lain, terbukti tidak memadai karena kurangnya insentif, model yang tepat dan dukungan dari pasar untuk mengatasi eksternalitasnya sementara masyarakat sipil kekurangan sumber daya, ide, dan keterampilan untuk berkembang. Oleh karena itu, konsep kolaborasi untuk menyelesaikan masalah ini muncul dengan crowdsourcing, khususnya model bisnis crowfunding. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis bagaimana platform digital crowdfunding mengelola inovasi sosial mereka dan bagaimana jaringan inovasi sosial mendukung mereka untuk mencapai tujuan mereka. Penelitian ini adalah penelitian kualitatif deskriptif dengan studi literatur, observasi partisipatif dan wawancara pada platform crowdfunding sebagai metode pengumpulan data ke dua platform crowdfunding terbesar Indonesia: Kitabisa.com dan Gandeng Tangan. Sebagai inovasi sosial, kedua perusahaan memiliki jaringan inovasi sosial yang berbeda tetapi menerapkan tahap-tahap inovasi sosial yang serupa, dari tahap perumusan ide hingga penskalaan dan difusi inovasi, tetapi keduanya masih dalam tahap pengembangan untuk menciptakan dampak sistemik pada inovasi sosial secara keseluruhan.Penelitian ini diharapkan memiliki implikasi praktis untuk pemberdayaan inovasi sosial yang diprakarsai oleh pemerintah atau sektor swasta dan implikasi teoretis tentang pengembangan manajemen inovasi berbasis kolaborasi untuk menyelesaikan masalah sosial dan ekonomi. Kebaruan penelitian penelitian ini terletak pada fokus penelitian yang membahas peran platform crowdfunding dalam menciptakan inovasi sosial yang belum banyak diteliti di Indonesia.Kata kunci: inovasi sosial, Indonesia, masalah sosial dan ekonomi, crowdfunding, platform digital